2019
DOI: 10.1080/01425692.2018.1540294
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of social class differentials in parent-initiated contact with teachers

Abstract: This article analyses the association between social class and parent-initiated contact with teachers. Hypotheses are derived from Lareau's theory on 'concerted cultivation' and status maintenance theory on rational educational decision-making. Data from a national survey on French students traversing secondary school are used to study social class differentials in parents' involvement in Grade 9 when students are about to proceed to an important transition from lower to upper secondary school. Linear probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Child-rearing practices are culturally oriented for both beliefs about hard work and ability as predictors of scholastic success. Meritocratic beliefs shed light on the rationality of parenting practices in a similar way as rational choice theories (Barg 2019). They are part of a mindset where concerted cultivation practices pay off.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Child-rearing practices are culturally oriented for both beliefs about hard work and ability as predictors of scholastic success. Meritocratic beliefs shed light on the rationality of parenting practices in a similar way as rational choice theories (Barg 2019). They are part of a mindset where concerted cultivation practices pay off.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers from different countries have sought to explain inequality by these micro-level interactions within families beyond the context of the United States (e.g. Barg 2019;Matsuoka 2019). With some nuances, the conclusion is similar: parents transmit differential advantages to children through parental practices.…”
Section: The Concept Of Concerted Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in various national contexts outside China have demonstrated that parent–teacher relations regarding their children's education are likely differ based on parents' social status: privileged parents tend to engage more actively with their children's teachers than less privileged parents (Barg 2019; Lareau and Weininger 2003).…”
Section: Social Disparities In Parent–teacher Relationsmentioning
confidence: 99%
“…Parent–teacher relations have played a significant role in children's educational experiences and outcomes (Epstein 2001; Mattingly et al 2002). However, research from various national contexts has shown that less privileged parents face various barriers in their relations with teachers compared to their more privileged counterparts (Barg 2019; Lareau and Weininger 2003; Reay 2002). Such barriers emerge from less privileged parents' social positions, which are measured, following a Bourdieusian lens, by the volume and composition of capital, mainly economic capital (e.g., as monetary or financial assets), and cultural capital (e.g., books, cultural experiences, and educational qualifications) (Bourdieu 1986; Crossley 2011).…”
Section: Introductionmentioning
confidence: 99%